2015
DOI: 10.1017/s1041610215000551
|View full text |Cite
|
Sign up to set email alerts
|

Telephone-based cognitive screening for stroke patients in china

Abstract: Both the telephone-based 5-minute NINDS-CSN protocol and SIS were feasible and valid in screening cognitive impairment after stroke in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In our study, the diagnostic accuracy of the MoCA 5-min protocol was comparable with the full MoCA, which was consistent with previous findings [4]. The AUC of the MoCA 5-min protocol was higher than the results of previous studies (AUC from 0.76 to 0.86) [4,7,12,13], which may be because different reference standards were utilized in these studies. Previous studies have reported lower diagnostic accuracy of the NINDS-CSN 5-min protocol as compared to the full MoCA [6,9], while the MoCA 5-min protocol performed equally well to the full MoCA [4], which is similar to the results from our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the diagnostic accuracy of the MoCA 5-min protocol was comparable with the full MoCA, which was consistent with previous findings [4]. The AUC of the MoCA 5-min protocol was higher than the results of previous studies (AUC from 0.76 to 0.86) [4,7,12,13], which may be because different reference standards were utilized in these studies. Previous studies have reported lower diagnostic accuracy of the NINDS-CSN 5-min protocol as compared to the full MoCA [6,9], while the MoCA 5-min protocol performed equally well to the full MoCA [4], which is similar to the results from our study.…”
Section: Discussionsupporting
confidence: 90%
“…orientation, delayed recall and verbal fluency) from the full MoCA like the NINDS-CSN 5 min protocol, but with minor modifications in the assessment instruction and the grading system. To date, only four studies examining the Chinese version of the MoCA 5-min protocol have been published (2 in Hong Kong and 2 in Nanjing) [4,7,12,13]. This protocol has shown an acceptable level of reliability, which includes test-retest reliability and internal consistency [4,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many screening instruments did not reach these values 67 , 14 , 19 , 20 , 24 , 27 , 38 , 42 - 45 , 48 , 61 , 62 , 66 , 69 Therefore, items need to be better studied and replaced to improve the quality of the instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The MoCA has demonstrated wide validity and reliability in several languages. However, researchers should exercise caution with MoCA cut-off points in each country because this test is influenced by educational level,45 , 58 , 60 , 61 age,60 cerebrovascular disease14 , 19 , 24 , 45 , 58 , 60 and time post-stroke 4957 Additionally, deficits in language (comprehension and expression) and perception (hemineglect), which are common post-stroke, may negatively affect the performance of participants on MoCA tasks.…”
Section: Discussionmentioning
confidence: 99%